Fluff spherical Co–Ni3S2/NF for enhanced hydrogen evolution. (30th July 2022) - Sun, Kaiyue; Qiao, Fen; Yang, Jing; Li, Haitao; Cui, Yi; Liu, Peng Fei
Abstract: Ni3 S2 is a kind of HER catalyst electrode with high efficiency and easy preparation. However, due to the weak electrochemical adsorption capacity of water molecules at the Ni site, it is not conducive to the dissociation of water molecules. At the same time, strong sulfur-hydrogen bond is easily formed at the S site, which greatly hinders the desorption and bonding of hydrogen atom to produce hydrogen. Hydrogen evolution performance of Ni3 S2 in alkaline media needs to be improved. In this paper, fluff spherical Co–Ni3 S2 was grown in situ on nickel foam by two-step hydrothermal method successfully. By doping cobalt ions, the strong interaction of S–H bond on Ni3 S2 surface was weakened, the adsorption and dissociation of water molecules were promoted, and the catalyst was exposed to more reactive centers, so as to improve the hydrogen evolution performance of cathodic reduction reaction. Electrochemical test and Transient Photovoltage (TPV) tests show that Co–Ni3 S2 has fast reaction kinetics and high electron transfer rate, especially it only needs 148 mV low overpotential to reach 10 mA cm −2 in 1.0 M KOH alkaline electrolyte, which is better than Ni3 S2 /NF (250 mV). In addition, Co–Ni3 S2 also has excellent electrochemical stability. Density functional theory (DFT) calculations confirm that the optimized adsorption energy enables the catalyst to exhibit excellent HER activity. This work provides useful guidance to construction of effective nickel related HER catalysts. Graphical abstract: This work reported fluff spherical Co–Ni3 S2 /NF obtained by a two-step hydrothermal method, and the surface of fluff spherical exhibits a rough nanowire structure. The structure exhibited excellent hydrogen evolution performance and good stability in alkaline environment. Image 1 Highlights: Fluff spherical Co–Ni3 S2 /NF were prepared by a two-step hydrothermal method. Co–Ni3 S2 /NF has lower overpotential than both Ni3 S2 /NF and NF. The abundant active sites are the key to promoting the hydrogen evolution performance.